Developmental response of Spodoptera litura Fab. to treatments of crude volatile oil from Piper betle L. and evaluation of toxicity to earthworm, Eudrilus eugeniae Kinb. (July 2016) - Vasantha-Srinivasan, Prabhakaran; Senthil-Nathan, Sengottayan; Thanigaivel, Annamalai; Edwin, Edward-Sam; Ponsankar, Athirstam; Selin-Rani, Selvaraj; Pradeepa, Venkatraman; Sakthi-Bhagavathy, Muthiah; Kalaivani, Kandaswamy; Hunter, Wayne B.; Duraipandiyan, Veeramuthu; Al-Dhabi, Naif Abdullah
Abstract: Evaluations of biological effects of (Pb-CVO) the crude volatile oil of Piper betle leaves on the tobacco cutworm Spodoptera litura were conducted. Pb-CVO was subjected to GC-MS analysis and twenty vital compounds were isolated from the betel leaf oil. Pb-CVO was tested at four different concentrations (0.25, 0.5, 1.0 and 1.5%) against S. litura . The treated insects exhibited dose depended mortality. The mortality rate was significantly higher at the 1.0 and 1.5% Pb-CVO. The LC50 (Lethal concentration) were observed at 0.48% Pb-CVO. Larval and pupal durations increased in all treatment concentrations (0.25, 0.3, 0.4 and 0.5%) whereas, pupal weight decreased compared to control. Adult longevity of S. litura was reduced in all treatments but predominantly in the 0.4 and 0.5% Pb-CVO. Correspondingly, mean fecundity rate was reduced at all concentrations compared to control. Histological studies of larvae mid-gut profiles of S. litura were severely damaged in 1.0 and 1.5% and showed abnormalities in mid-gut cells with 0.25 and 0.5% Pb-CVO treatments. Earthworm toxicity illustrated that 0.1% of chemical insecticides (monocrotophos and cypermethrin) varied widely in their contact toxicities compared to 0.5 and 1.0% Pb-CVO and control in both contact filter paper and artificial soil test. These findings suggest that twenty essential compounds of betel leaf oil were significant inhibitors of the development and caused behavioral changes of S. litura . Treatment with betel leaf oil at these concentrations had no adverse effect on earthworm populations. Graphical abstract: Highlights: Twenty major compounds of CVO of Piper betle were detected through GCMS analysis. CVO of P. betle significantly alters the behavior of Spodoptera litura. Histological changes in the gut tissues of S. litura treated with CVO of P. betle were observed. Earthworm toxicity showed no significant difference in treatment with CVO of P. betle comparable to chemical pesticides.